Diskresi Sebagai Penerapan Nilai-Nilai Moralitas dan Etika Dalam Penyelenggaran Pemerintahan Daerah - indra wijaya; ahmad firman; basri rakhman (Badan Penelitian dan Pengembangan Daerah Kota Makassar, 2022)
Discretion has the potential to be exercised by government officials in conducting engineering or fraud, because of the existence of these government authorities they can freely take the initiative to develop or formulate policies by taking advantage of certain conditions, cases that occur very often and the new order. Basically, freedom of action is oriented to the welfare of the community and in line with this, it is expected that discretion as an authority or government authority applies freedom of action or discretion which is actually used for the benefit of society in the current era of globalization.